Paraguay : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The report provides an overview of the recent economic developments in Paraguay. The study analyzes the potential output, growth, prices, wages, and the labor market; and assesses the public finances, social security, and public enterprises. The paper reviews the monetary sector, evaluates the soundness of the banking sector and its developments, the external sector by assessing the balance-of-payments developments and the exchange and trade system. The study also provides a statistical appendix report of the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet